Do you feel safe with your robot? Factors influencing perceived safety in human-robot interaction based on subjective and objective measures. Issue 158 (February 2022) - Akalin, Neziha; Kristoffersson, Annica; Loutfi, Amy
Highlights: The key influencing factors of perceived safety are identified as comfort, experience/familiarity, predictability, sense of control, transparency, and trust. The quantifiable measures occur under unsafe conditions. We should focus on understanding the conditions that humans feel unsafe rather than they feel safe. Concerning the objective and subjective measures, robot-related and human-related factors should be treated together due to the bidirectional nature of the HRI. Physiological signal data can supplement the subjective reports for evaluating perceived safety. Individual human characteristics, emotional and physiological reactions as well as the interrelationship between the identified factors should be taken into account to better understand the source of decreased safety perception. Abstract: Safety in human-robot interaction can be divided into physical safety and perceived safety, where the latter is still under-addressed in the literature. Investigating perceived safety in human-robot interaction requires a multidisciplinary perspective. Indeed, perceived safety is often considered as being associated with several common factors studied in other disciplines, i.e., comfort, predictability, sense of control, and trust. In this paper, we investigated the relationship between these factors and perceived safety in human-robot interaction using subjective and objective measures. We conducted a two-by-five mixed-subjects design experiment. There were two between-subjects conditions: the faulty robot was experienced at the beginning or the end of the interaction. The five within-subjects conditions correspond to (1) baseline, and the manipulations of robot behaviors to stimulate: (2) discomfort, (3) decreased perceived safety, (4) decreased sense of control and (5) distrust. The idea of triggering a deprivation of these factors was motivated by the definition of safety in the literature where safety is often defined by the absence of it. Twenty-seven young adult participants took part in the experiments. Participants were asked to answer questionnaires that measure the manipulated factors after within-subjects conditions. Besides questionnaire data, we collected objective measures such as videos and physiological data. The questionnaire results show a correlation between comfort, sense of control, trust, and perceived safety. Since these factors are the main factors that influence perceived safety, they should be considered in human-robot interaction design decisions. We also discuss the effect of individual human characteristics (such as personality and gender) that they could be predictors of perceived safety. We used the physiological signal data and facial affect from videos for estimating perceived safety where participants' subjective ratings were utilized as labels. The data from objective measures revealed that the prediction rate was higher from physiological signal data. This paper can play an important role in the goal of better understanding perceived safety in human-robot interaction.